Influencia de la granulometría y tipo de concentrador en la recuperación y ley de oro mediante gravimetría - Iglesias Carrasco, Maicol Arnold (2023)
The variables of influence of particle size (percentage passing 200 mesh) and type of gravimetric concentrator on gold recovery (%) and gold grade (g/t) were investigated using a composite sample of three ores from the Pataz area, with the following chemical composition: 6.47 g/t Au and 16.26 g/t Ag. A bifactorial design was used, with the variable granulometry evaluated at levels 35, 45 and 55 % passing through 200 mesh and the type of concentrator: Wilfley type gravity table and Icon i150 centrifugal concentrator, the dependent variable being the percentage of gold recovery and the gold grade (g/t). Concentrate was obtained with gravimetric table at 35% - #200, gold recovery 67.70 % and grade of 9.94 g/t, at 45% - #200, gold recovery 63.16 % and grade of 12.45 g/t, at 55% - #200, gold recovery 56.12 % and grade of 17.84 g/t. With centrifugal concentrator was obtained at 35% - #200, gold recovery 24.70 % and grade of 24.24 g/t, at 45% - #200, gold recovery 38.60 % and grade of 35.68 g/t, at 55% - #200, gold recovery 47.30 % and grade of 42.19 g/t. According to the results, for the analysis of variance for gold recovery and gold grade, P=0.000 was obtained for the particle size, P=0.000 for the type of gravimetric concentrator, and P=0.000 for the interaction of both variables, it can be concluded that the particle size (% passing 200 mesh) and type of gravimetric concentrator significantly influence gold recovery and gold grade.